ARE FOREIGN AID AND ECONOMIC GROWTH POSITIVELY RELATED? EMPIRICAL EVIDENCE FROM BANGLADESH - Hussain, Shahadat; Rahman, Md. Habibur (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
As an emerging country, the progress of Bangladesh is highly promising. Foreign aid may be one of the key players fueling such advancement. The note is an attempt to examine the effect of foreign aid on the economic growth of Bangladesh. With a view to fulfill our objective, the study employs annual time series data during the period of 1971 to 2019. It has used some econometric tools i.e., Unit Root Tests and OLS Methods to process the collected data. The dependent variable is Gross Domestic Product (GDP) while other independent variables i.e., Foreign Aid (ODA), Gross Capital Formation (GCF), Population (POP), and Education (EDU). The test results confirmed that GDP growth is positively related to foreign aid, gross capital formation, and education, but negatively related to population. In Bangladesh, if foreign aid increases by 1% then the GDP growth, gross capital formation, and education rate will accelerate to 0.1988%, 0.6015%, and 0.0652% respectively. So it is evident that foreign aid plays a propitious role to progress the economic growth of Bangladesh. It is a crying need to swell up effectiveness, transparency, proper accountability in allocation, and stronger management of aid inflows to speed up economic growth. JEL Classification Codes: F2, I2, O4.